Stålverk 80 i Luleå : Statens roll i den lokala samhällsplaneringen - Hägglund, Johan (2015)
This paper examines the role of the Swedish national government in the societal development in Luleå following the plans considering Steeleworks 80 (Stålverk 80). Guiding research questions have been: what help did the local government except to get from the national government for the societal development and what help did it actually get? In the empirical chapter of the essay the development of three different neighborhoods – Hertsön, Porsön, and Björkskatan – are examined through the case study method. The Board minutes of the local government is used as main source. The conclusion finds that the national government almost exclusively aided through financial support. Those findings are related to earlier studies where the national government has shown to aid in societal development in a number of different policy instruments. Validerat; 20151106 (global_studentproject_submitter)